Konflik DPR, Pemerintah, dan Masyarakat tentang Persyaratan Dukungan Partai di UU Pemilu: Studi Kasus Mahkamah Konstitusi 2019 - Aditya Nugraha; Chusnul Mar'iyah (Syntax Corporation Indonesia, 2024)
The purpose of the study is to analyze the policy process of the requirement for the election of the President of 20 percent of the House of Representatives seats or obtaining 25 percent of the valid votes nationally in the previous election of members of the House of Representatives and how the pros and cons are in the House of Representatives. This study uses a qualitative research method. Research that uses qualitative methods is research that interprets data by giving meaning to the data obtained. In this study, there are two data collection techniques using primary and secondary data sources that are complementary in explanating the discussion in this study. As a result, political conflicts arise because of the presidential threshold in the 2017 Election Law. It divides the actors between those who support deletion and those who resist. Political parties, community activists, and new groups are involved. The conflict reflects the battle of interests between the old and new political oligarchs. Petitions for removal often fail due to a lack of constitutional support.